Poxvirus infecfion in turkeys - Ideris, Aini; Ibrahim, A. Latif (Persatuan Doktor Veterinar Malaysia, 1986)
A case of poxvirus infection ill a flock of turkeys is reported. The affected turkeys had nodular wartlike growths of various sizes and shapes on the unfeathered skill of face, around the eyelids and on the feet. Electron microscopic examination of the scabs from the affected turkeys and pock lesions on chorioallantoic membrane revealed typical pox virions.